Exploration and Research on the Idea of Ecological Civilization Quality Education for College Students under the Background of “Internet +” - Genhong Chen (Advances in Multimedia, 2022)
In order to improve the effect of ecological civilization quality education (ECQE) for college students under the background of “Internet +,” this paper combines the AHP method to construct an intelligent analysis model. Moreover, this paper introduces the improved analytic hierarchy process and database technology into the ECQE system and uses the AHP algorithm to make the system produce more objective and scientific results. At the same time, the system overcomes the individual subjectivity of decision-makers, improves the effectiveness of decision-making, and makes the entire decision-making process easier to implement. In addition, this paper combines the improved algorithm to construct an ECQE model for college students under the background of “Internet +.” Based on the experimental research results, it can be seen that the ECQE model for college students proposed in this paper has a good effect under the background of “Internet +.”